Exploring loss and grief during the COVID-19 pandemic: a scoping review of qualitative studies - Tao, Xinyu (2023)
The COVID-19 pandemic has brought about multiple losses to various groups, namely patients, families and healthcare professionals. Grief, which is the reaction to these losses, could cause strain on these individuals' physical and mental health if not identified and managed early. This scoping review analysed loss, grief and how they were managed among these groups during the pandemic.